DETERMINAN FAKTOR SPESIFIK BANK TERHADAP NON-PERFORMING LOAN GROSS DAN NON-PERFORMING LOAN NET PADA BANK PEMBANGUNAN DAERAH - Diah Wahyuningsih (UNIVERSITAS INDRAPRASTA PGRI, 2021)
This study aims to analyze the influence of bank-specific factors on Non-Performing Loan Gross (NPL gross) and Non-Performing Loan Net (NPL net) in Regional Development Banks 2009-2018. Bank-specific factors used in this study are the Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM). The method used is panel data which is a combination of cross-section and time series. The results of this study indicate that CAR has a negative and significant effect on NPL gross, but has no effect on the NPL net. ROA has a negative and not significant effect on NPL gross but has a negative and significant effect on NPL net. ROE has a negative and significant effect on NPL gross and NPL net. While the LDR and NIM have a positive and significant effect on NPL gross and NPL net.